Numerical Analysis of Airflow in Trachea Affected by Thyroid Cancer Using Finite Volume Method - Fatahillah, Arif; Jannah, Miftahul; Setiawani, Susi; Setiawan, Toto Bara; Kristiana, Arika Indah (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
The study aims to analyze the airflow in the trachea due to thyroid cancer. Thyroid cancer is a cancer that attacks the thyroid gland. The thyroid gland is located in the neck below the Adam's apple. In general, thyroid cancer causes stenosis of the trachea due to cancer compression of the tracheal wall. This problem is solved using the finite volume method with SIMPLE (Semi Implicit Method for Pressure Linked Equation) discretization. This method is well suited for the discretization of irregularly shaped fluid flows. The software used is Matlab and Ansys Fluent. Matlab is used to compute numerical solutions and display graphs, while Fluent is used to visualize the air flow. The result of this study is that the greater the percentage of stenosis, the velocity of the airflow is faster and the pressure of the airflow is lower. The most critical condition for respiratory power loss is when the airflow velocity exceeds the normal limit, i.e. when the narrowing is more than 50%, the initial velocity is more than 0,1 m/s.